Research Trends on Lesson Study Based on Google Scholar and Scopus Database: a Bibliometric Analysis - Deda, Yohanis Ndapa; Disnawati, Hermina; Daniel, Otaget (Jurnal VARIDIKA, 2023)
This study investigates lesson study research trends through bibliometric analysis on widely distributed Google Scholar (GS) and Scopus databases. We reviewed 997 papers from GS and 200 documents from the Scopus database searched using Harzing's Publish on May 6 2023. A descriptive study approach was used to investigate the data. The result of this study is that the number of lesson study documents has increased over the last decade (2012-2022). The most productive author based on GS  is R Huang from the United States, and the full author based on Scopus is E. Saito from Australia. While the prominent authors based on the highest citations are Fernandez Yoshida, based on GS, and Dudley, with the highest citations based on Scopus. The “International Journal for Lesson and Learning Studies” in the last decade is the most source of lesson study documents. Based on VosViewer visualization, Rosa is the author who has the most co-authorship papers and total link strength. The VosViewer displays four clusters related to lesson study: community, context, observation, and participation. Our strong recommendations regarding this study are lesson study research related to literacy, numeracy, and mathematical abilities. The results can assist relevant researchers in understanding trends in lesson study research and recommend guidelines for other studies.